Preparation and Characterization of an Unsupported Nano-MoS2 Catalyst - Zhu, Yuqin; Guo, Fan (Asian Journal of Chemistry, 2013)
Nano-sized unsupported MoS2 hydrodesulphurization catalysts were synthesized using a novel and mainly hydrothermal, reduction method. The structures of the catalysts, their specific surface areas, mean particle sizes and micro-morphologies were characterized and analyzed. It was the first time that MoS2 with a specific surface area of as high as 412 m2 g-1 area was obtained successfully. Most of the MoS2 had the shape of stacked platelets (slab < 8), which were between 30 and 40 nm long and 2.0 to 3.5 nm in diameter. It was found that the MoS2 fibres were readily-flexed and contained many defects, which increased the number of active sites on the catalyst: thus they were easily able to meet the requirements of deep hydro-treatment type desulphurization of diesel oil.